Carcinicultura: licenciamento, fiscalização e monitoramento no Estado do Ceará - Cavalcante, Maria Dias (2005)
Environmental Licensing process is a planning instrument that aims environmental control, conservation, improvement and recovery in order to garantee social and economic development in consonance with the principles of sustainable development. In this sense, it was evaluated the environmental Licensing implemented by the state of Ceará for instalation of carciniculture farms, considering the fast growth of the activity in the state, given the existence of great propitious areas to its development. This research analyzed the procedures adopted by Superintendência Estadual do Meio Ambiente - SEMACE for installation of new shrimp companies and regularization of unauthorized shrimp farming as well as the imposed measures for those who have entered illegally Areas of Permanent Preservation ( such as margin of rivers, mangrove etc.). Shrimp farms impacts and implemented control measures and monitoring were identified. An analysis was proceeded from the conflicts in relation to the development of the activity in the state, especially as for technical concepts and environmental licensing. Beyond bibliographical research, the survey involved: interviews with environment agencies controllers, technician responsible for the analysis of licensing processes, professional specialists and living communities of surrounding areas; analyses of the processes protocols in the environment agency; analysis of the applied legislation and visits to shrimp farms.